Broad ligament pregnancy - a rare form of ectopic - Sonak, Mangala; Chaubey, Arya; Harikanth, Disha Rama; Waikar, Manjushri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ectopic pregnancy in the broad ligament is a serious form of extrauterine pregnancy which is very rare. The diagnosis is very difficult to establish especially in acute cases leading to many complications and maternal morbidity and mortality. We present the case of 22-weeks-old abdominal pregnancy who underwent emergency laparotomy for acute symptoms before her complete diagnostic evaluation. Ruptured broad ligament pregnancy was noted with hemoperitoneum. The patient recovered completely after surgery and was discharged in a stable condition. The diagnosis of broad ligament pregnancy is difficult to establish and challenging to manage because of its rarity, varied presentation and intra-operative complications. High chances of morbidity and mortality in both mother and foetus prompts increased awareness among both obstetricians and patients.